Peran Financial Ratio dan ESG Score terhadap Stock Price: Indonesia - Moch Lutfi Gunawan; Dicky Jhoansyah; Resa Nurmala (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The purpose of this study is to determine the effect of Price to Earnings Ratio (PER) and Governance Score on the stock price of transportation and logistics companies listed on the IDX from 2022 to 2023. An associative quantitative method was used in this study, as well as multiple linear regression analysis to determine the state of the dependent variable with two independent variables that influence it. To ensure the validity of the statistical model used, classical assumption tests were conducted. A total of 16 companies were analyzed, with data collected over two consecutive years. The analysis revealed that, simultaneously, the PER and Governance Score variables have a positive and significant influence on Stock Price. Similarly, on a partial basis, the PER variable has a positive and significant influence on Stock Price, and Governance Score has a positive and significant influence on Stock Price. These results indicate that financial and non-financial elements, particularly those related to PER and Governance Score, play a crucial role in shaping Stock Price in the capital market. Therefore, companies must prioritize and continuously improve their financial performance, transparency practices, managerial effectiveness, and compliance with governance principles to create value for stakeholders and attract investor interest.